2010
DOI: 10.2486/indhealth.48.283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Low Back Pain among Thai and Myanmar Migrant Seafood Processing Factory Workers in Samut Sakorn Province, Thailand

Abstract: Low back pain (LBP) is one of the most common health problems all over the world. The lifetime prevalence of low back pain is reported to be over 70% in European countries and the peak prevalence occurred between ages 35 and 55 in the working population 1) . Despite its benign nature, LBP is the leading cause of disability and the highest cost for workers' compensation in industrialized countries [2][3][4][5][6] . In Thailand as well, high prevalence of LBP is reported. The six month prevalence of LBP was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 33 publications
5
39
3
1
Order By: Relevance
“…The higher risk of work-related injuries in younger workers has been reported in Western countries 1,17,26,40,41) . Some previous studies on workers in some industries reported that age was a risk factor for LBP 8,33,42,43) , while other studies reported no association between age and LBP 8,39) . The results of this study did not show an association between age and injury or LBP among kitchen workers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The higher risk of work-related injuries in younger workers has been reported in Western countries 1,17,26,40,41) . Some previous studies on workers in some industries reported that age was a risk factor for LBP 8,33,42,43) , while other studies reported no association between age and LBP 8,39) . The results of this study did not show an association between age and injury or LBP among kitchen workers.…”
Section: Discussionmentioning
confidence: 93%
“…Information on personal factors consisted of gender, age, obesity and body height. Age was categorized as middle-aged and older (≥40 yr) group and younger (<40 yr) group referring to previous research 5,8,33) . Obesity was defined as body mass index ≥25 kg/m 2 according to the international classification for Asian populations recommended by WHO 34) .…”
Section: Questionnairementioning
confidence: 99%
“…Usually it resolves within a few weeks. The most common risk factor for low back pain of women are heavy physical workload, lifting, awkward posture, static work posture, pregnancy, pushing & pulling, body vibration, increased body mass index and life style 11 . Bangladesh is a land of grueling poverty in terms of economic sense.…”
Section: Duration Of Painmentioning
confidence: 99%
“…Researcher also found that most of the slum women with LBP were less educated, 41% illiterate, 22% completed primary level, 17% SSC level, 10% HSC level. A Thai study stated that 46.1% were educated upto primary level who had back pain 11 .…”
Section: Precipitates Work Position For Painmentioning
confidence: 99%
“…5%. [29], [7], [47]. The lifetime prevalence of low back pain (LBP) was reported to be over 70 percent in industrialized countries [9], [48].…”
Section: Introductionmentioning
confidence: 99%